Charge discharge studies of LiNii.xCoxFey02 cathode materials / Nur Fatin Farhanah Nazarudin - Nazarudin, Nur Fatin Farhanah (2012)
Final Year Project Report Submitted in Partial Fulfillment of the Requirements for the Degree of Bachelor of Science (Hons.) Industrial Physics in the Faculty of Applied Science Universiti Teknologi MARA JULY 2012 Prof. Dr. Norlida Kamarulzaman Three active materials are used for the fabrication of Li-ion cells. They are; LiNio8Coo.1Feo.1O2, LiNio.7Coo.2Feo.1O2, and LiNio.6Coo.3Feo.1O2 using a mix and cast technique. The fabricated cathode was assembled in a coin cell configuration and all this was done in an Ar filled glove box. The anode used was lithium foil and the electrolyte used was 1M LiPF6 in EC/DMC (1/1 V/V). The separator used was microporous polypropylene film. The cell was tested using an automated battery cycler. The electrochemical charge discharge cycling was done by using a constant current of 1.0mA (charge-discharge) within a voltage range of 4.3V to 3.0V. Results show charge-discharge time for the three cathode materials from the first cycle to third cycle differs for different stoichiometries.